The Crosstalk between Fat Homeostasis and Liver Regional Immunity in NAFLD - Minjuan Ma; Rui Duan; Hong Zhong; Tingming Liang; Li Guo (Journal of Immunology Research)
The liver is well known as the center of glucose and lipid metabolism in the human body. It also functions as an immune organ. Previous studies have suggested that liver nonparenchymal cells are crucial in the progression of NAFLD. In recent years, NAFLD’s threat to human health has been becoming a global issue. And by far, there is no effective treatment for NAFLD. Liver nonparenchymal cells are stimulated by lipid antigens, adipokines, or other factors, and secreted immune factors can alter the expression of key proteins such as SREBP-1c, ChREBP, and PPARγ to regulate lipid metabolism, thus affecting the pathological process of NAFLD. Interestingly, some ncRNAs (including miRNAs and lncRNAs) participate in the pathological process of NAFLD by changing body fat homeostasis. And even some ncRNAs could regulate the activity of HSCs, thereby affecting the progression of inflammation and fibrosis in the course of NAFLD. In conclusion, immunotherapy could be an effective way to treat NAFLD.